Innovative Application of Three-Dimensional-Printed Breast Model-Aided Reduction Mammaplasty - Xiong, Shaoheng; E, Bei; Zhang, Zhaoxiang; Tang, Jiezhang; Rong, Xiangke; Gong, Haibo; Yi, Chenggang (Frontiers in Surgery, 2022)
Symptomatic macromastia places a severe physical and psychological burden on patients. Reduction mammaplasty is the primary treatment; however, conventional surgery may lead to postoperative nipple-areolar complex necrosis due to damage to the dominant supplying arteries. In this study, we designed and fabricated an innovative, three-dimensional-printed breast vascular model to provide surgical guidance for reduction mammaplasty. Preoperative computed tomography angiography scanning data of patients were collected. The data were then processed and reconstructed using the E3D digital medical modeling software (version 17.06); the reconstructions were then printed into a personalized model using stereolithography. The three-dimensional-printed breast vascular model was thus developed for individualized preoperative surgical design. This individualized model could be used to intuitively visualize the dominant supplying arteries' spatial location in the breasts, thereby allowing effective surgical planning for reduction mammaplasty. The three-dimensional-printed breast vascular model can therefore provide an individualized preoperative design and patient education, avoid necrosis of the nipple-areolar complex, shorten operation duration, and ensure safe and effective surgery in patients.